1997
DOI: 10.1016/s0735-1097(97)00158-7
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Endogenous Antioxidant Activity and Inhibition of Lipid Peroxidation as Common Mechanisms of Antiatherosclerotic Effects of Vitamin E, Lovastatin and Amlodipine

Abstract: This study suggests that a reduction in lipid peroxidation and preservation of SOD may be common mechanisms of antiatherosclerotic effects of lovastatin, vitamin E and amlodipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(117 citation statements)
references
References 35 publications
6
109
0
2
Order By: Relevance
“…More importantly, we also demonstrated that either of two calcium channel blockades, amlodipine or manidipine, effectively suppressed this type of overexpression, suggesting that these agents acted as the antioxidant in the present experiments. The antioxidant effects of amlodipine have been previously reported (37,57). It is likely that calcium channel blockades exert their anti-inflammatory effects by blocking the main source of oxidative stress, without affecting the antioxidant system, which was found to be upregulated by L-NAME-treatment in the present study (as shown by the representative data from studies of Mn-SOD).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…More importantly, we also demonstrated that either of two calcium channel blockades, amlodipine or manidipine, effectively suppressed this type of overexpression, suggesting that these agents acted as the antioxidant in the present experiments. The antioxidant effects of amlodipine have been previously reported (37,57). It is likely that calcium channel blockades exert their anti-inflammatory effects by blocking the main source of oxidative stress, without affecting the antioxidant system, which was found to be upregulated by L-NAME-treatment in the present study (as shown by the representative data from studies of Mn-SOD).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, these agents reduce cardiovascular mortality in patients after myocardial infarction (36). The calcium channel blockade amlodipine has been shown to limit the progression of arteriosclerosis and atherosclerosis in animals and humans (37,38). Although the mechanisms underlying the direct protective effects of calcium channel blockades on endothelial cell injury are not fully understood, such vasoprotective effects as the amelioration of endothelial dysfunction (39,40) and decreases in the proliferation of vascular smooth muscle cells (41), oxidative stress (37,42), and inflammation (43), are at least in part independent of the blood pressure-lowering effects of these agents.…”
Section: Introductionmentioning
confidence: 99%
“…A rabbit chow containing 1% cholesterol and 4% coconut oil diet was chosen because other investigators have demonstrated that when given for a period of 10 to 12 weeks, it results in marked elevation in serum cholesterol and induction of diffuse, aortic atherosclerosis. [11][12][13] At the end of the 10-week dietary intervention, food was withdrawn for 12 hours, and the rabbits were weighed and then anesthetized with intravenous sodium pentobarbital (50 mg/kg). Venous blood samples were obtained for measurement of serum cholesterol, and aortas were excised for examination of atherosclerotic area (aorta), Ang II receptor binding, and determination of vasoreactivity.…”
Section: Hypercholesterolemic Rabbitsmentioning
confidence: 99%
“…11 Al-though the extent of atherosclerosis in different blood vessels of rabbits fed a high-cholesterol diet varies significantly, this model has been used extensively to study pathogenetic aspects of atherosclerosis and its modulation by various agents. [11][12][13] The current study was designed to examine Ang II receptor expression in vascular tissues and its relationship with vasoreactivity and atherogenesis in a rabbit model of atherosclerosis induced by feeding of a high-cholesterol diet.…”
mentioning
confidence: 99%
“…Thus, amlodipine has been demonstrated to have antioxidant properties in atherosclerotic animal models, but its effect on endothelial function has not been extensively assessed in humans. 32 Recently, Anderson et al 23 reported that amlodipine did not improve reactive hyperaemic blood flow in peripheral arteries of patients with coronary disease in contrast to the improvement observed with quinapril.…”
Section: S36mentioning
confidence: 98%